2021
DOI: 10.21203/rs.3.rs-969304/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic insights into rapid speciation within the world’s largest tree genus

Abstract: Species radiations have long fascinated biologists, but the contribution of adaptation to observed diversity and speciation is still an open question. Here, we explore this question using the clove genus, Syzygium, the world’s largest genus of tree species comprising approximately 1200 species. We dissect Syzygium diversity through shotgun sequencing of 182 distinct species and 58 additional as-yet unidentified taxa, and assess their genetic diversity against a chromosome-level reference genome of the sea appl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Their work on Vitaceae suggested that 10× coverage genome sequencing data was optimum to assemble a sufficient number of high-quality nuclear genes for phylogenetic inference (Liu et al, 2021a). Low et al (2022) illustrated how DGS data can provide evidence both for investigating phylogeny and speciation processes in recently radiated groups. Using 30 Gb of WGS data for each of 289 Syzygium individuals, they generated parallel genome-wide SNPs, single-copy nuclear genes, as well as plastomic data sets to reconstruct well-supported phylogenies.…”
Section: Deep Genome Skimmingmentioning
confidence: 99%
“…Their work on Vitaceae suggested that 10× coverage genome sequencing data was optimum to assemble a sufficient number of high-quality nuclear genes for phylogenetic inference (Liu et al, 2021a). Low et al (2022) illustrated how DGS data can provide evidence both for investigating phylogeny and speciation processes in recently radiated groups. Using 30 Gb of WGS data for each of 289 Syzygium individuals, they generated parallel genome-wide SNPs, single-copy nuclear genes, as well as plastomic data sets to reconstruct well-supported phylogenies.…”
Section: Deep Genome Skimmingmentioning
confidence: 99%
“…This species is known only from two collections made between 1961-1971 and more efforts are needed to document this species carefully in its habitat and to reassess its range, population size and threats considering almost all tropical rainforest regions have been identified as biodiversity hotspots (Myers et al 2000;Nic Lughadha et al 2020). Notes: Phylogenetic studies (see Harrington and Gadek, 2004;Biffin et al 2006;Low et al 2021) have shown Syzygium species with calycine calyptra derive from multiple lineages and anatomical analysis (Vasconcelos et al 2020) indicates that closed Syzygium calyces have multiple developmental origins. As a result, locating the species most closely related to Syzygium nusatenggaraense will be a challenge, further compounded by the lack of a complete inventory of Syzygium species occurring in the Lesser Sunda Islands and surrounding regions.…”
Section: Phenologymentioning
confidence: 99%
“…However, the genus was not recognised by subsequent workers (such as Henderson, 1949;Kochummen, 1978;Hyland, 1983) due to lack of corroborative evidence acquired from anatomical studies (Dadswell and Ingle, 1947;Ingle and Dadswell, 1953;Pike, 1956;Schmid, 1972). Results obtained from molecular phylogenetic analyses showed Cleistocalyx to be polyphyletic; members of the genus were found to have derived from multiple lineages across the Syzygium phylogeny (Harrington and Gadek, 2004;Biffin et al 2006;Craven and Biffin, 2010;Vasconcelos et al 2020;Low et al 2021). In addition, molecular results supported uniting of the various segregate syzygioid genera such as Acmena DC., Jambosa Adans., Piliocalyx Brongn.…”
Section: Introductionmentioning
confidence: 99%